2001
DOI: 10.1021/bi0155448
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Metal Receptor Sites in Escherichia coli Zur, an Ultrasensitive Zinc(II) Metalloregulatory Protein

Abstract: The Escherichia coli Zur protein is a Fur homologue that regulates expression of Zn(II) uptake systems. The zinc-loaded form of Zur is proposed to bind DNA and repress transcription of the znuABC genes. Recent in vitro data indicate that the transcriptional activity of Zur is half-maximal when free Zn(II) concentrations are in the sub-femtomolar range, making it the most sensitive Zn(II) metalloregulatory protein reported to date. Previous results indicate that Zur binds at least one zinc; however, little else… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…For example, we hypothesize that cadmium could induce the znuABC operon by replacing zinc in metal-binding sites of Zur, thereby affecting its transcriptional activity. In fact, it has already shown that metal replacement in DNAbinding proteins can alter their substrate specificity (Predki and Sarkar 1994) and that the substitution of zinc with cobalt in Zur is associated to a change in the metal coordination environment (Outten et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we hypothesize that cadmium could induce the znuABC operon by replacing zinc in metal-binding sites of Zur, thereby affecting its transcriptional activity. In fact, it has already shown that metal replacement in DNAbinding proteins can alter their substrate specificity (Predki and Sarkar 1994) and that the substitution of zinc with cobalt in Zur is associated to a change in the metal coordination environment (Outten et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, one cysteine that is conserved among the Zur proteins is absent from the B. burgdorferi Fur. E. coli Zur has two metal binding sites that bind zinc in part through coordination with cysteines (41). Which cysteines are involved is not yet known; however, a cysteine uniquely conserved among the Zur proteins seems a likely candidate.…”
Section: Vol 186 2004mentioning
confidence: 99%
“…In Escherichia coli (Brocklehurst et al, 1999;Outten et al, 2001), Bacillus subtilis (Gaballa and Helmann, 1998;Gaballa et al, 2002) and Saccharomyces cerevisiae (Zhao and Eide, 1997;Jamison McDaniels et al, 1999;Daniels et al, 2002;Bird et al, 2003) a large number of genes were identified encoding metallo-regulatory proteins that act as zinc sensors and transcriptional activators and/or repressors. Zinc finger-containing transcription factors not only regulate 'zinc-sensitive' genes, but also control their own transcription through a positive autoregulatory mechanism (Lyons et al, 2000).…”
Section: Zinc Participates In Gene Expression Controlmentioning
confidence: 99%